(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2021)
The article considers the main problems of forming an integrated system of social-adaptive management of the organization. It is determined that integrated social-adaptive management is management, the concept of which is aimed at reconciling the needs, capabilities and interests of employees, consumers, organizations and society. The article also highlights the main elements of the system, which allowed to understand its construction and in parallel explored its structural and functional connections and relationships based on the mechanism of reconciling the needs and interests of customers, business and society as a whole. In addition, we propose the principles and model of external and internal infrastructure of the integrated system of social-adaptive management of the organization based on international and domestic standards of interaction between organization and society, taking into account global, national, regional and corporate features of external and internal environment and mutual development in the future.